2017
DOI: 10.1016/j.jaci.2016.12.978
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune and inflammatory manifestations occur frequently in patients with primary immunodeficiencies

Abstract: Our results provide the basis for a detailed prospective evaluation of autoimmunity and inflammation in the context of PIDs, with a view to accurately assessing these risks and describing the possible effect of medical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
199
3
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(222 citation statements)
references
References 30 publications
10
199
3
10
Order By: Relevance
“…Nearly a quarter of patients presented with symptoms other than recurrent infections. Non‐infectious presentations such as autoimmune cytopaenias, inflammatory bowel disease and malignancy are being recognized increasingly as possible presentations of PID . The median diagnostic delay for patients who presented with malignancy is 4 years, the highest amongst the presenting symptoms recorded by our registry.…”
Section: Discussionmentioning
confidence: 95%
“…Nearly a quarter of patients presented with symptoms other than recurrent infections. Non‐infectious presentations such as autoimmune cytopaenias, inflammatory bowel disease and malignancy are being recognized increasingly as possible presentations of PID . The median diagnostic delay for patients who presented with malignancy is 4 years, the highest amongst the presenting symptoms recorded by our registry.…”
Section: Discussionmentioning
confidence: 95%
“…This prevalence of autoimmune cytopenia is strikingly higher than among the general population, in whom ITP has been estimated to affect between 8 and 12 in 100,000 [14]; AIHA between 1 and 17 per 100,000 [15, 16]; and autoimmune neutropenia 1 in 100,000, among in children aged 1 to 10 years [17]. Compared to the USIDNET Registry, other CVID patient registries report higher prevalence of autoimmune cytopenias: a French report of 408 CVID patients and a US cohort of 473 CVID patients noted one or more autoimmune cytopenia in 14 to 18% of patients [4, 8, 18]. While 13.2 and 14.2% of CVID patients had a diagnosis of ITP in the French and New York cohorts respectively, only 7.4% were noted as having had ITP in USIDNET.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prevalence of these complications in the +AC CVID patients suggests that these conditions originate from the immune dysregulation and dysfunction contributing to their specific CVID phenotype. Further, the conditions that were increased in the +AC group have been associated with increased morbidity and mortality [3, 4, 18]. As the first episode of autoimmune cytopenia most often develops early in the course of CVID [810, 19, 20], autoimmune cytopenia may predict a more complicated course, necessitating closer monitoring for various non-infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…In this paradigm, immune deficiency ultimately predisposes to exaggerated inflammatory responses and indeed, is increasingly recognized today in the field of primary immunodeficiencies (PIDs) . A recent analysis of French National Primary Immunodeficiencies Registry (CEDEDIH) showed that one or more autoimmune/inflammatory symptoms are observed in 26.2% of patients with primary immunodeficiency . This paradox of immune deficiency leading to compensatory inflammation is only recently appreciated, as traditionally immune deficiency was only associated with infection susceptibility.…”
Section: Concluding: the Paradox Of Immune Deficiency And Inflammatiomentioning
confidence: 99%